Moses and Abraham Maimonides encountering the Divine - Lobel, Diana (Boston, MA Academic Studies Press, 2021)
Frontmatter -- Index -- Acknowledgements -- Introduction -- Part One: Moses and Abraham Maimonides on Created Light, Created Word, and the Event at Mount Sinai -- 1. Abraham Maimonides on Created Light in the Cleft of the Rock: Exodus 33:22 -- 2. Maimonides on Created Light: An Esoteric Interpretation -- 3. Abraham and Moses Maimonides on Cloud and Glory: Exodus 16:9-10/Guide III:9 -- 4. Abraham Maimonides on Created Light in the Preparation for the Sinai Event -- 5. Maimonides on the Theophany at Mount Sinai -- 6. Abraham Maimonides on the Created Word at Mount Sinai: Between Maimonides and R. Abraham he-Ḥasid -- 7. Abraham and Moses Maimonides on Created Light in the Vision of the Nobles -- Part Two: Ehyeh asher Ehyeh and the Tetragrammaton: Between Eternity and Necessary Existence -- 8. Introduction: Ehyeh asher Ehyeh and the Tetragrammaton -- 9. Rabbinic Interpretations of Ehyeh asher Ehyeh -- 10. The Interpretation of Saadya Gaon -- 11. Saadya's Long Commentary to Exodus 3:13-15 -- 12. Abraham Maimonides on Saadya Gaon -- 13. The Interpretation of Maimonides -- 14. Abraham on Eternity and Relationship -- Conclusion -- Notes -- Bibliography -- Index
Moses Maimonides-a proud heir to the Andalusian tradition of Aristotelian philosophy-crafted a bold and original philosophical interpretation of Torah and Judaism. His son Abraham Maimonides is a fascinating maverick whose Torah commentary mediates between the philosophical interpretations of his father, the contextual approach of Biblical exegetes such as Saadya, and the Sufi-flavored illuminative mysticism of his Egyptian Pietist circle. This pioneering study explores the intersecting approaches of Moses and Abraham Maimonides to the spark of divine illumination and revelation of the divine name Ehyeh asher Ehyeh, "I am that I am / I will be who I will be."
Mode of access: Internet via World Wide Web.
In English
Keywords: God (Judaism) -- Name; God (Judaism); Presence of God; Revelation -- Judaism; RELIGION / Judaism / Kabbalah & Mysticism; Abraham Maimonides; Aristotelian; Islam; Jewish mysticism; Judaism; Maimuni; Moses Maimonides; Sufism; Torah; biblical commentary; divine Names; medieval philosophy; religious studies; revelation; theology